Influence mechanism of Cd ion soaking on performance of flexible CZTSSe thin film solar cells. (February 2022) - Sun, Luanhong; Wang, Wei; Hao, Lingyun; Jia, Zhichao; Zhao, Yijie; Zhi, Guowei; Yao, Hanyu
Abstract: Realizing flexible Cu2 ZnSn(S, Se)4 (CZTSSe) thin film solar cell with high efficiency and excellent mechanical durability has always been a challenging task in green demanded era. In this work, Cu2 Cdx Zn1-x Sn(S, Se)4 (CCZTSSe) absorber was synthesized by selenizing Cd 2+ treated CZTS precursor. Due to the powerful ability of Cd 2+ soaking in boosting grain growth, the grain size of CCZTSSe was remarkably increased from nano to micron level. Cd atom actually act entering into the lattice and replaces Zn location in the post-selenization process. The band gap of CCZTSSe exhibits a decreasing trend (1.37 eV–1.29 eV) as x increases from 0 to 0.13. In comparison to CZTSSe absorber without Cd 2+ soaking treatment, Cu2 Cdx Zn1-x Sn(S, Se)4 (x = 0.03, 0.07 and 0.13) can establish the heterojunction with better matching effect with CdS buffer layer, demonstrating an enhanced conduction band offset (CBO). The improved heterojunction characteristic substantially prevents carrier recombination caused by interface state defects, which can be the crucial reason of the enhanced device performance. Finally, for x = 0.07, the device efficiency was optimized to 4.38%. This systematic work offers a novel solution for vital problems encountered in flexible CZTSSe thin film solar cells, which can lead to prospective applications in wearable devices.